PERBEDAAN BODY MASS INDEX (BMI), PORSI KALORI KONSUMSI MAKAN PADA TUKANG BATU DAN KARYAWAN UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Wistha Miyaki (FKU 16 UMY 077, 2016)
Based on health research of Riset Kesehatan Dasar (Riskesdas) (Depkes RI., 2007),, men and women in the age â‰¥ 15 years who have a body mass index (BMI)> 25 kg / mÂ² was 13.9% and 23.8%. Budiyanto (2002) mentions some of the causes of obesity is an imbalance of diet intake with physical daily activity. The purpose of this research is to determine the difference in body mass index (BMI), the share of consumption of calories eaten in a mason and employees of the University of Muhammadiyah Yogyakarta. Methods: This study used prospectively study design that is analytic survey with a cros-sectional approach which is a quantitative research. The technique used is purposive sampling using inclusion and exclusion criteria. Respondents consisted of 30 employees of the University of Muhammadiyah Yogyakarta (UMY) that consists of the Bureau of Human Resources (BSDM) as many as 6 people, 1 person from the Bureau of Law (Biro Hukum), Public Bureau (Biro Umum) as many as 12 people, the Bureau of New Student Admissions (Biro Penerimaan Mahasiswa Baru) as many as 6 people and agencies, the Board of the Daily Trustees (BPH) as 5 and 30 bricklayers that worked at SMA N 1 Bungah Tanjung, kecamatan Teramang Jaya, kabupaten Mukomuko of Kota Bengkulu number 8, working on building projects in SMK 1 Mandi Angin, kecamatan Teramang Jaya, kabupaten Mukomuko of Kota Bengkulu number 7, a builder which was worked in a private home with a street address, Jalan Hibrida 10 Gading Cempaka kelurahan Sidomulyo Kota Bengkulu as many as 6 people, builders are again working on building projects for students boarding around the campus of the University of Muhammadiyah Yogyakarta (UMY) as many as 9 people. Measurement of weight using scale Gea brand and height using micotoise staturmeter 200 cm and nutrition scales sitting using nhonnhoa brand. Data analysis using SPSS software program that is paired samples t-test. Results: The results of the analysis obtained for the value of Body Mass Index(BMI) that has counted equal to 2.178 with sig is 0,038 and for the value portion of calories t -5.640 with 0.000 sig. It can be concluded that there are differences in Body Mass Index (BMI), the share of consumption of calories eaten by the bricklayers and the employees of the University of Muhammadiyah Yogyakarta. Body Mass Index (BMI) of the employees of UMY greater than the BMI of the bricklayers, while the portion of calories of the bricklayers is greater than the portion of calories of the employees of UMY